Influence of hyperbaric oxygen on blood vessel reactivity : concept of changes in conducted vasomotor response - Drenjančević, Ines (Array, 2009)
Abstract: The actions of oxygen in the body are extremely complex, and are also involved in various signalling pathways. Hyperbaric oxygen is known to contribute to the improvement of conditions where tissue circulation is suboptimal, and has considerable usage in different treatment protocols and experimental investigations. However, the precise mechanism by which hyperbaric oxygen changes the functioning of coordinated blood vessel systems and microcirculation is still unknown. Taking into account the known facts, we suggest that hyperbaric oxygen induces changes in conducted vasomotor responses, and in that way influences vascular sensitivity and reactivity to vasodilators and vasoconstrictors. Conducted vasomotor responses are constrictions and dilations that are propagated along the vessel, leading to changes in vessel diameter on a certain distance of the initial site of vasoactive substance activity. Because these vascular responses are of substantial significance in physiological processes, their modification would subsequently cause alterations of blood vessel function and tissue perfusion that could explain observed effects of hyperbaric oxygen. We also discuss potential molecular targets of hyperbaric oxygen, investigation of which could presumably help in the eventual clarification of hyperbaric oxygen action